Typologies of co-production of public services: A scale proposal - Gouveia Junior, Antonio; Bezerra, Joacil Carlos Viana; Cavalcante, Carlos Eduardo (Contextus - Revista Contemporânea de Economia e Gestão, 2023)
The objective of this work was to create a scale of typologies of co-production of public services. For this, the steps for building scales proposed by Costa (2011) were followed. The exploratory phase took place in the form of an integrative literature review and item generation. Meanwhile, the descriptive phase details the procedures for constructing and validating the scale. The scale consists of 5 factors (preliminary, initial, basic, intermediate and advanced) and 19 items generated from 301 valid responses. The research presents its contributions by delivering a scale that is both capable of measuring the different ways citizens see co-production and has the potential to contribute to future studies.